Relative age effect? No "flipping" way! Apparatus dependent inverse relative age effects in elite, women`s artistic gymnastics - Langham-Walsh, E.; Gottwald, V.; Hardy, J. (PLOS ONE, 2021)
In contrast to research on team-sports, delayed maturation has been observed in higher-skilled gymnasts, leading to atypical distributions of the relative age effect. Recent studies have reported intra-sport differences in the relative age effect and given the task demands across gymnastics apparatus, we expected to find evidence for the influence of apparatus specialism. We examined the presence of a relative age effects within a sample of elite, international, women`s artistic gymnasts (N = 806, Ncountries = 87), and further sampled our data from vault, bars, beam, and floor major competition finalists. Poisson regression analysis indicated no relative age effect in the full sample (p = .55; R2 adj. = .01) but an effect that manifested when analysing apparatus independently. The Index of Discrimination (ID) analysis provided evidence of an inverse relative age effect identified for beam (p = .01; ID = 1.27; R2 adj. = .12), a finding that was corroborated by a marginal effect in our vault finalists (p = .08; ID = 1.21; R2 adj. = .06). These novel findings can be attributed to the integrated influence of self-fulfilling prophecy upon coach and gymnast expectations, as well as the technical mechanisms underpinning skill development involved in the underdog hypothesis.